If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7n+3=-12+4n+8
We move all terms to the left:
-7n+3-(-12+4n+8)=0
We add all the numbers together, and all the variables
-7n-(4n-4)+3=0
We get rid of parentheses
-7n-4n+4+3=0
We add all the numbers together, and all the variables
-11n+7=0
We move all terms containing n to the left, all other terms to the right
-11n=-7
n=-7/-11
n=7/11
| 3q–11=4 | | -2-3•-8r+2=160 | | 21-9(8-6x)=22/8*x | | 21-9(8-6x)=22/8*4 | | (X+3)+13=3x | | t4– 2= 1 | | 22x+12=56 | | 22-9(8-6x)=22/8*x | | 7+2b=15 | | 12/20n=-2/7 | | 0.375x-1.875=0.12x+1.185 | | 60-x=59 | | 4/3b+2=4−1/3b | | (3/8p)-(4/9)=(5/8p)+7 | | 4x+16=x/5 | | 20=5+3u | | v/5.2=-81.9 | | -5b–-19b+-13b–12b=11 | | 13x+142=107 | | -6x-12=-6 | | f4(0.5f−0.25)=6+f | | 2/7(x+4)=6 | | 3/8p-4/9=5/8p+7 | | −6.5(x-5)=18.2 | | 22-9(8-6x)=22/8*4 | | √(x^2)-36=8 | | -7x^2+x-6=0 | | −6.5(x−5)=18.2 | | 66x-43=617 | | X-4{(-6c/5)+(16/3)}-3c=-16 | | −6.5(n−5)=18.2 | | J(x)=3x-12 |